The Impact of Moral Emotions on Cause-Related Marketing Campaigns: A Cross-Cultural Examination - Kim, Jae-Eun; Johnson, Kim K. P. (2013)
This research was focused on investigating why some consumers might support cause-related marketing campaigns for reasons other than personal benefit by examining the influence of moral emotions and cultural orientation. The authors investigated the extent to which moral emotions operate differently across a cultural variable (US versus Korea) and an individual difference variable (self-construal). A survey method was utilised. Data were collected from a convenience sample of US (n = 180) and Korean (n = 191) undergraduates. Moral emotions significantly influenced purchase intention for a social-cause product. The influence of an ego-focused moral emotion (i.e., pride) on purchase intention was greater for US than Korean participants. The influence of another-focused moral emotion (i.e., guilt) on purchase intention was greater for high-interdependent participants than for low-interdependent participants. The findings of this research provide important and relevant implications to marketers and policy makers in developing persuasive messages and customer relationship programmes.
Keywords: Self-construal; Moral emotion; Culture; Cause-related marketing